2018
DOI: 10.1007/s10661-018-6696-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring concentration and isotopic composition of methane in groundwater in the Utica Shale hydraulic fracturing region of Ohio

Abstract: Degradation of groundwater quality is a primary public concern in rural hydraulic fracturing areas. Previous studies have shown that natural gas methane (CH) is present in groundwater near shale gas wells in the Marcellus Shale of Pennsylvania, but did not have pre-drilling baseline measurements. Here, we present the results of a free public water testing program in the Utica Shale of Ohio, where we measured CH concentration, CH stable isotopic composition, and pH and conductivity along temporal and spatial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…For example, instances of methane occurrence in groundwater reported in some of observational studies (Molofsky et al 2013;Li and Carlson 2014;Siegel et al 2015;McMahon et al 2017) were not spatially correlated with locations of oil and gas wells, which could further confirm the migration of methane to different distances and directions from the gas well. Our simulations corroborate the results of previous studies that methane observation in groundwater is not concentrically aligned around the leakage source (Jackson et al 2013;Steelman et al 2017;Cahill et al 2017;Rice et al 2018a;Moortgat et al 2018;Botner et al 2018). • The low-permeability layer, i.e., claystone, is assumed to be horizontal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, instances of methane occurrence in groundwater reported in some of observational studies (Molofsky et al 2013;Li and Carlson 2014;Siegel et al 2015;McMahon et al 2017) were not spatially correlated with locations of oil and gas wells, which could further confirm the migration of methane to different distances and directions from the gas well. Our simulations corroborate the results of previous studies that methane observation in groundwater is not concentrically aligned around the leakage source (Jackson et al 2013;Steelman et al 2017;Cahill et al 2017;Rice et al 2018a;Moortgat et al 2018;Botner et al 2018). • The low-permeability layer, i.e., claystone, is assumed to be horizontal.…”
Section: Discussionsupporting
confidence: 92%
“…Some observational is being analyzed. The top panels show the geometry of the claystone layers at shallow depths, in black color studies (Molofsky et al 2013;Li and Carlson 2014;Siegel et al 2015;McMahon et al 2017;Nicot et al 2017;Botner et al 2018) found no correlation between thermogenic methane in water samples from groundwater wells and just the distance to hydrocarbon wells corroborating our findings.…”
Section: Comparison With Field Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, the degassing is clearly determined by a geologic structure: a fault-controlled pockmark. Radiocarbon dating of CH 4 could clarify if the gas is modern or fossil, e.g., [52].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, few studies have documented such variations (e.g. : Coleman and McElreath, 2012;Gorody, 2012;Humez et al, 2015;Sherwood et al, 2016;Smith et al, 2016;Currell et al, 2017, Botner et al, 2018 and they have relied on only a few wells and/or on a few sampling events.…”
Section: Objectivementioning
confidence: 99%